Field notes contributed by John Van Dyk, spring 1996 - Van Dyk, John, 1936-et al (1996)
Spring report of birds found in northwest Iowa contributed by John Van Dyk. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1996. Epson - sheet feed